Relationships and implications of biological determinism, the Freudian thought of criminal psychology, and the new criminology - Ríos Patio, Gino (2017)
The author analyzes the new impulse of biological determinism, the Freudian thought of criminal psychology, in the current neoliberal moment and the so-called scientific paradigm of the new criminology, especially that of critical criminology, focusing on their relationships and implications, that is, the connections, contradictions and consequences between those and these, with the purpose of reflecting on the causes of criminality from its personal criminological position. The objective of the article is to evaluate the functionality of the biological and psychological deterministic approaches of criminality in the current scientific paradigm of critical criminology. As a result of the correlation analysis, it is concluded that the schools of clinical and psychological criminology do not sufficiently explain the cause of crime today.